2006
DOI: 10.1080/09658210544000024
|View full text |Cite
|
Sign up to set email alerts
|

A content analysis of involuntary autobiographical memories: Examining the positivity effect in old age

Abstract: Although research on autobiographical memory is growing steadily, very little is known about involuntary autobiographical memories that are spontaneously recalled in everyday life. In addition, very few studies have examined the actual content of autobiographical memories and how the content might change as a function of age. The present study carried out a content analysis of involuntary autobiographical memories recorded by young (N = 11) and old (N = 10) volunteers over a period of 1 week. A total of 224 me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
98
0
2

Year Published

2007
2007
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(109 citation statements)
references
References 49 publications
9
98
0
2
Order By: Relevance
“…The most frequent category for the directive memories was stressful events, whereas the most frequent categories for the self-, social, and control memories were school, person, periences at work or university); romantic involvement (e.g., being intimate, romantic dinners, receiving gifts for Valentine's Day); school (e.g., experiences at school-including high school and folk high school); deaths/funerals; special occasions (e.g., birthdays, weddings, engagements, parties); births; traveling/journeys; war/ army; and miscellaneous. The coding was carried out in accordance with the guidelines described by Schlagman et al (2006). We first attempted to classify each memory so that the category captured all of the themes mentioned in the memory description.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequent category for the directive memories was stressful events, whereas the most frequent categories for the self-, social, and control memories were school, person, periences at work or university); romantic involvement (e.g., being intimate, romantic dinners, receiving gifts for Valentine's Day); school (e.g., experiences at school-including high school and folk high school); deaths/funerals; special occasions (e.g., birthdays, weddings, engagements, parties); births; traveling/journeys; war/ army; and miscellaneous. The coding was carried out in accordance with the guidelines described by Schlagman et al (2006). We first attempted to classify each memory so that the category captured all of the themes mentioned in the memory description.…”
Section: Resultsmentioning
confidence: 99%
“…In order to examine the emotional content of the memories, we first categorized the memory descriptions according to 17 content categories obtained in a different study (Schlagman, Schulz, & Kvavilashvili, 2006). We used this coding system because it is based on one of the most systematic content analyses of autobiographical memories to date and was derived independent of an interest in memory functions.…”
Section: Methodsmentioning
confidence: 99%
“…Because not all event records could be identified according to one of the life script categories, a variable number of non-life-script events was seen for all four event types. Table 5 shows the distribution of such non-life-script events according to the 17 content categories identified by Schlagman et al (2006). Table 5 shows that accidents/ illnesses and stressful events accounted for 34% of the important past (non-life-script) events and 15% of the wordcued past events, whereas these negative event categories were extremely rare in the two future conditions.…”
Section: Content Analysesmentioning
confidence: 99%
“…These findings are consistent with earlier work showing that future episodic thinking involves less sensory imagery and more schemabased construction than does episodic remembering. In contrast to our prediction, future events did not refer more rized by two independent raters, using the 17 memory content categories developed by Schlagman, Schulz, and Kvavilashvili (2006 Idyll. Two raters scored all memories and future event representations on a 3-point rating scale on how idyllic they were (Berntsen & Jacobsen, 2008).…”
Section: Future Versus Past Events In the Word-cued Versus Important mentioning
confidence: 99%
“…In addition, in Study 1, it was not quite clear whether participants rated the emotional valence of their memories per se, the original event when they first experienced it, or a mixture of both. Previous research has shown that retrospective evaluations of negative emotions become less intense over time (Walker, Vogl, & Thompson, 1997) and that-at least in older adults-ratings of autobiographical memories become more positive over time (Field, 1981;Kennedy, Mather, & Carstensen, 2004;Levine & Bluck, 1997;Schlagman, Schulz, & Kvavilashvili, 2006). To address this issue, an additional question requesting ratings of the pleasantness of the original event when it first occurred was included; that is, we distinguished between the pleasantness of the memory and of the original event.…”
Section: Comparing the Retrieval Context Of Laboratory And Diary Invomentioning
confidence: 99%